2016
DOI: 10.1111/acel.12549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-31-5p, miR-141-3p, miR-200c-3p, and GLT1 as human liver aging markers sensitive to donor-recipient age-mismatch in transplants

Abstract: SummaryTo understand why livers from aged donors are successfully used for transplants, we looked for markers of liver aging in 71 biopsies from donors aged 12–92 years before transplants and in 11 biopsies after transplants with high donor–recipient age‐mismatch. We also assessed liver function in 36 age‐mismatched recipients. The major findings were the following: (i) miR‐31‐5p, miR‐141‐3p, and miR‐200c‐3p increased with age, as assessed by microRNAs (miRs) and mRNA transcript profiling in 12 biopsies and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…However, evidence related to their role in other cell types could be an indication to understand their potential effect when increasing in RBCs. miR-31-5p is increased in aging endothelial cells isolated from umbilical cords, and it is considered as a human liver aging marker since it increases in livers of old age donors [37,38]. A recent study shows that miR-203a induces apoptosis in human scar fibroblasts [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence related to their role in other cell types could be an indication to understand their potential effect when increasing in RBCs. miR-31-5p is increased in aging endothelial cells isolated from umbilical cords, and it is considered as a human liver aging marker since it increases in livers of old age donors [37,38]. A recent study shows that miR-203a induces apoptosis in human scar fibroblasts [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR‐31a‐5p has been reported to directly target bone relevant markers, such as RUNX2, OSX, and DKK1 (Baglio, Devescovi, Granchi, & Baldini, 2013; Deng, Wu et al., 2013; Gao et al., 2011; Lv et al., 2017). Furthermore, it has been reported that regulation of miR‐31a‐5p expression could be used to modulate senescence‐related pathological conditions such as cancer, and the aging process (Capri et al., 2017; Cho, Dimri, & Dimri, 2015), which highlights us the important role of miR‐31a‐5p in cellular senescence. Moreover, according to a previous study, miR‐31a‐5p controls osteoclast formation and facilitates IL‐2 production in T cells by targeting RhoA (Fan et al., 2012; Mizoguchi, Murakami, Saito, Miyasaka, & Kohsaka, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…36,39,40 In humans, miR-31 is associated with aging livers and is increased in tumors, correlating with cirrhosis. 28,41,42 significant elevation of this miRNA in sera observed less than 2 months after the AFB 1 dosing period and considerably before diagnosis (sacrifice). It is remarkable that this increase is maintained throughout the lifetimes of the animals during such a complex and multifactorial disease like cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Rno‐miR‐31a‐5p is increased in plasma after liver injury and differs from its human homolog hsa‐miR‐31 by one nucleotide . In humans, miR‐31 is associated with aging livers and is increased in tumors, correlating with cirrhosis . Other miRNAs found upregulated in tumors, such as the miR‐200 family (eg rno‐miRs‐200b‐3p, 429, 141‐3p) and rno‐miR‐205 are known to play a role in angiogenesis and epithelial to mesenchymal transition in multiple cancers including HCC .…”
Section: Discussionmentioning
confidence: 99%